PRODUCTION OF ECO-ENZYME AS A WASTE AWARENESS INITIATIVE AT MCC LEARNING HOUSE IN RUTONG - Novianty C Tuhumury; Alex S W Retraubun; Frederika S Pello; Mintje Wawo; James Abrahamsz; Cyecilia Pical; Meysy de Fretes (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
A simple and environmentally friendly solution to waste management is the use of eco-enzyme, which offers numerous benefits. Knowledge about eco-enzyme is important to be disseminated to the community, particularly among school-aged children. This community service activity was conducted with the aim of training children at the MCC Learning House to process fruit peel waste into eco-enzyme. The activity took place at the MCC Learning House in Rutong and was attended by 20 participants. The methods employed included lectures and hands-on training on the production of eco-enzyme from pineapple and banana peel waste. The team, together with the participants, practiced the eco-enzyme production process, beginning with an explanation of the functions and uses of the prepared tools and materials. This was followed by weighing brown sugar and fruit peels according to the specified ratio, after which water was added and the mixture was placed into plastic containers and labeled. Following the training, all participants gained an understanding of eco-enzyme. As a closing activity, the community service team and participants took a group photograph.